Judgments of responsibility : a foundation for a theory of social conduct - Weiner, Bernard (Guilford, 1995)
(Abbreviated) The anatomy of responsibility Responsibility and achievement evaluation Responsibility and stigmatization AIDS and stigmatization Responsibility, stigmatization, mental illness, and the family Helping behavior Aggression Reducing inferences of responsibility: Excuses and confession On the construction of psychological theory and other issues